Energy Exchange Between Electromagnetic Ion Cyclotron (EMIC) Waves and Thermal Plasma: From Theory to Observations - Usanova, M. E. (Frontiers in Astronomy and Space Sciences, 2021)
The cold plasmaspheric plasma, the ring current and the radiation belts constitute three important populations of the inner magnetosphere. The overlap region between these populations gives rise to wave-particle interactions between different plasma species and wave modes observed in the magnetosphere, in particular, electromagnetic ion cyclotron (EMIC) waves. These waves can resonantly interact with multiple particle species, being an important loss process for both ring current ions and radiation belt electrons, as well as a cold plasma heating mechanism. This mini-review will focus on the interaction between EMIC waves and cold and thermal plasma, specifically the role of EMIC waves in cold and thermal electron and ion heating. It will discuss early theoretical results in conjunction with numerical modelling and recent satellite observations, and address outstanding problems and controversies in this field.